Contagion of Fear : Is the Impact of COVID-19 on Sovereign Risk Really Indiscriminate? - Cevik, Serhan; Ozturkkal, Belma (Washington, D.C. : International Monetary Fund, 2020)
This paper investigates the impact of infectious diseases on the evolution of sovereign credit default swap (CDS) spreads for a panel of 77 advanced and developing countries. Using annual data over the 2004-2020 period, we find that infectious-disease outbreaks have no discernible effect on CDS spreads, after controlling for macroeconomic and institutional factors. However, our granular analysis using high-frequency (daily) data indicates that the COVID-19 pandemic has had a significant impact on market-implied sovereign default risk. This adverse effect appears to be more pronounced in advanced economies, which may reflect the greater severity of the pandemic and depth of the ensuing economic crisis in these countries as well as widespread underreporting in developing countries due to differences in testing availability and institutional capacity. While our analysis also shows that more stringent domestic containment measures help lower sovereign CDS spreads, the macro-fiscal cost of efforts aimed at curbing the spread of the disease could undermine credit worthiness and eventually push the cost of borrowing higher.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet